2013
DOI: 10.1093/hmg/ddt456
|View full text |Cite
|
Sign up to set email alerts
|

Tsc1 deficiency-mediated mTOR hyperactivation in vascular endothelial cells causes angiogenesis defects and embryonic lethality

Abstract: This is a study on the role of tuberous sclerosis complex1 (TSC1) mutation and mTOR activation in endothelial cells during angiogenic and embryonic development. Past studies had shown that Tsc1/Tsc2 mutant genes lead to overactivation of mTOR in the regulating pathways in developing fetus. We used conditional Cre-loxp gene knockout approach to delete Tsc1 in mice's endothelial cells in our experimental models. Similarly, activation of mTOR signaling in endothelial cells of these embryos (Tie2-Cre/Tsc1(-/-)) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 56 publications
3
27
0
1
Order By: Relevance
“…IF staining indicated that DEPTOR expression was decreased in vascular ECs in KO mice comparing with WT mice as shown in Fig. 1C and D. Cluster of differentiation 31 (CD31) was used primarily to show the presence of endothelial cells, which helped to evaluate the degree of angiogenesis [22]. Taken together, the results showed that there was DEPTOR deficiency in ECs of Tek- Cre + /Deptor fl/fl mice compared with WT mice.…”
Section: Resultsmentioning
confidence: 90%
“…IF staining indicated that DEPTOR expression was decreased in vascular ECs in KO mice comparing with WT mice as shown in Fig. 1C and D. Cluster of differentiation 31 (CD31) was used primarily to show the presence of endothelial cells, which helped to evaluate the degree of angiogenesis [22]. Taken together, the results showed that there was DEPTOR deficiency in ECs of Tek- Cre + /Deptor fl/fl mice compared with WT mice.…”
Section: Resultsmentioning
confidence: 90%
“…Previous studies reported that the survival rate of dopaminergic neurons collected at embryonic day 14 was ~17-21%, which was higher than that of cells collected at embryonic day 16 or later, which was only 0.1-2.5% (18,19). In addition, a previous study confirmed that ~90% of dopaminergic neurons are clustered around a tissue region of 1.0 mm 3 in rostral mesencephalic tegmentum (20).…”
Section: Discussionmentioning
confidence: 88%
“…Although there is a likely benefit to this treatment, reduction in hemorrhagic risk with mTORi has not been formally demonstrated since bleeding events were infrequent in randomised trials [3]. The specific effect of the mTORi on the vascular component of the AML is not known but experimental data suggest that mTORis could partially inhibit the vascular pathogenesis of TSC [7]. …”
Section: Discussionmentioning
confidence: 99%